Research on Surface Roughness of Supersonic Vibration Auxiliary Side Milling for Titanium Alloy - Xuetao Wei; Caixu Yue; Desheng Hu; Xianli Liu; Yunpeng Ding; Steven Y. Liang (Chinese Journal of Mechanical Engineering, 2022)
Abstract The processed surface contour shape is extracted with the finite element simulation software. The difference value of contour shape change is used as the parameters of balancing surface roughness to construct finite element model of supersonic vibration milling in cutting stability domain. The surface roughness trial scheme is designed in the orthogonal test design method to analyze the surface roughness test result in the response surface methodology. The surface roughness prediction model is established and optimized. Finally, the surface roughness finite element simulation prediction model is verified by experiments. The research results show that, compared with the experiment results, the error range of the finite element simulation model is 27.5%–30.9%, and the error range of the empirical model obtained by the response surface method is between 4.4% and 12.3%. So, the model in this paper is accurate and will provide the theoretical basis for the optimization study of the auxiliary milling process of supersonic vibration.